HUBUNGAN ANTARA HARDINESS DAN DUKUNGAN SOSIAL TERHADAP STRES PENGASUHAN PADA IBU YANG MEMILIKI ANAK TUNAGRAHITA - Olianda, Rani Amelia; Rizal, Gumi Langerya (ATTA`DIB, 2020)
The Relationship Between Hardiness And Social Support On Parenting Stress In Mothers Who Have Mentally Retarded Children. This study aims to determine the relationship between hardiness and social support on parenting stress in mothers with mentally retarded children. The sampling method in this study used purposive sampling, the subjects in this study were 28 mothers who had children with mental retardation. The measuring instruments used are the hardiness scale, social support scale, and parenting stress scale. The data analysis technique used is regression analysis. The results showed that there was a relationship between hardiness and social support on parenting stress. The hardiness variable gave a greater contribution to parenting stress than the social support variable. The implications of this study are expected to be mothers with mentally retarded children can increase the hardiness in him and constantly seek social support from those closest to mitigate the effects of parenting stress.